Improving organs-at-risk sparing for choroidal melanoma patients: A CT-based two-beam strategy in ocular proton therapy with a dedicated eyeline. (June 2022) - Fleury, Emmanuelle; Trnková, Petra; van Rij, Caroline; Rodrigues, Myra; Klaver, Yvonne; Spruijt, Kees; Naus, Nicole; Zolnay, Andras; Pignol, Jean-Philippe; Kiliç, Emine; Hoogeman, Mischa S.
Highlights: A two-beam arrangement in ocular proton therapy has been investigated. T1 and T2 posterior choroidal tumors would benefit most from this strategy. This leads to improved anterior region and sclera sparing. The cost to the optic nerve is clinically acceptable. Delivering the two beams the same day is radiobiologically better. Abstract: Purpose: To investigate the potential clinical benefit of a two-beam arrangement technique using three-dimensional (3D) imaging of uveal melanoma (UM) patients treated with proton therapy and a dedicated eyeline. Material/Methods: Retrospective CT-based treatment plans of 39 UM patients performed using a single beam (SB) were compared to plans with two beams (TB) optimized for better trade-offs in organs-at-risk sparing. The RBE-weighted prescribed dose was 60 Gy ( D RBE, GTV  = 60 Gy) in four fractions, assuming an RBE of 1.1. Dosimetric findings were analyzed for three patient groups based on tumor-optic nerve distance and UM staging (group GrA: ≤3 mm, T1 T2 UM; GrB: ≤3 mm, T3 UM; GrC: >3 mm, T1 T2 T3 UM). Finally, two schedules were compared on biologically effective dose (BED): both beams being delivered either the same day (TB), or on alternate days (TBalter). Results: All strategies resulted in dosimetrically acceptable plans. A dose reduction to the anterior structures was achieved in 23/39 cases with the two-beam plans. D25% was significantly lowered compared to SB plans by 12.4 and 15.4 Gy RBE-weighted median dose in GrA and GrB, respectively. D2% was reduced by 18.6 and 6.0 Gy RBE-weighted median dose in GrA and GrB, respectively. A cost to the optic nerve was observed with a median difference up to 3.8 Gy RBE-weighted dose in GrB. BED differences were statistically significant for all considered parameters in favor of two beams delivered the same day. Conclusion: A two-beam strategy appears beneficial for posterior tumors abutting the optic nerve. This strategy might have a positive impact on the risk of ocular complications.